AQP1-Driven Migration Is Independent of Other Known Adverse Factors but Requires a Hypoxic Undifferentiated Cell Profile in Neuroblastoma - Nicola Pini; Zihe Huo; Urs Kym; Stefan Holland-Cunz; Stephanie J. Gros (MDPI AG, 2021)
Neuroblastoma is a biologically very heterogeneous tumor with its clinical manifestation ranging from spontaneous regression to highly aggressive metastatic disease. Several adverse factors have been linked to oncogenesis, tumor progression and metastases of neuroblastoma including NMYC amplification, the neural adhesion molecule NCAM, as well as CXCR4 as a promoter of metastases. In this study, we investigate to what extent the expression of AQP1 in neuroblastoma correlates with changing cellular factors such as the hypoxic status, differentiation, expression of known adverse factors such as NMYC and NCAM, and CXCR4-related metastatic spread. Our results show that while AQP1 expression leads to an increased migratory behavior of neuroblastoma cells under hypoxic conditions, we find that hypoxia is associated with a reduction of NMYC in the same cells. A similar effect can be observed when using the tetracycline driven mechanism of SH-EP/Tet cells. When NMYC is not expressed, the expression of AQP1 is increased together with an increased expression of HIF-1α and HIF-2α. We furthermore show that when growing cells in different cell densities, they express AQP1, HIF-1α, HIF-2α, NMYC and NCAM to different degrees. AQP1 expression correlates with a hypoxic profile of these cells with increased HIF-1α and HIF-2α expression, as well as with NMYC and NCAM expression in two out of three neuroblastoma cell lines. When investigating cell properties of the cells that actually migrate, we find that the increased APQ1 expression in the migrated cells correlates with an increased NMYC and NCAM expression again in two out of three cell lines. Expression of the tumor cell homing marker CXCR4 varies between different tumor areas and between cell lines. While some migrated tumor cells highly express CXCR4, cells of other origin do not. In the initial phase of migration, we determined a dominant role of AQP1 expression of migrating cells in the scratch assay.